Pharmacokinetics of Hyperthermic Intrathoracic Chemotherapy following Pleurectomy and Decortication. (5th April 2012) - Sugarbaker, Paul H.; Stuart, O. Anthony; Eger, Christopher
Abstract : In patients with pseudomyxoma peritonei or peritoneal mesothelioma, direct extension of disease through the hemidiaphragm may result in an isolated progression of tumor within the pleural space. We monitored the intrapleural and plasma levels of mitomycin C and doxorubicin by HPLC assay in order to determine the pharmacokinetic behavior of this intracavitary use of chemotherapy. Our results showed a persistent high concentration of intrapleural drug as compared to plasma concentrations. The increased exposure for mitomycin C was 96, and the increased exposure for doxorubicin was 241. When the clearance of chemotherapy from the thoracic cavity was compared to clearance from the abdomen and pelvis, there was a considerably more rapid clearance from the abdomen as compared to the thorax. The pharmacologic study of intrapleural chemotherapy in these patients provides a strong pharmacologic rationale for regional chemotherapy in this group of patients.